2016
DOI: 10.1007/s40806-016-0050-z
|View full text |Cite
|
Sign up to set email alerts
|

Quantifying Common Criticisms of Evolutionary Psychology

Abstract: In a sample of academics (N = 111), we quantified the dimensions underlying criticisms of evolutionary psychology in relation to criticisms of its parent fields (i.e., general psychology and evolutionary biology) and examined how various demographic and sociopolitical individual differences were related to these criticism dimensions. The five primary criticisms of evolutionary psychology reflected conceptual concerns, concerns over political implications, concerns over sampling, concerns about the validity of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 47 publications
0
12
0
2
Order By: Relevance
“…This is a novel perspective that can add to the existing debate between feminists and evolutionary psychologists, and it highlights the harm that EP studies can cause to marginalized groups. In addition, our results can provide insight as to why some scholars (Jonason and Schmitt, 2016) have found that gay and bisexual individuals have negative views of evolutionary psychology.…”
Section: Discussionmentioning
confidence: 75%
See 4 more Smart Citations
“…This is a novel perspective that can add to the existing debate between feminists and evolutionary psychologists, and it highlights the harm that EP studies can cause to marginalized groups. In addition, our results can provide insight as to why some scholars (Jonason and Schmitt, 2016) have found that gay and bisexual individuals have negative views of evolutionary psychology.…”
Section: Discussionmentioning
confidence: 75%
“…This rise in popularity has not come without controversy. Jonason and Schmitt (2016) found there is more criticism of EP than either of its parent fields, i.e. general psychology and evolutionary biology.…”
Section: Evolutionary Psychology and Lgbtq+ Issues: A Qualitative Stumentioning
confidence: 99%
See 3 more Smart Citations